Effect of Sowing Dates and Stage of Pinching on Growth, Yield and Quality of Fenugreek (Trigonella foenum-graecum L.) - Sowmya, P. T.; Naruka, I. S.; Shaktawat, R. P. S.; Kushwah, S. S. (International Journal of Bio-resource and Stress Management, 2023)
An experiment entitled effect of sowing dates and stage of pinching on growth, yield and quality of fenugreek was carried out during September 2015 to March 2016 at RVSKVV College of Horticulture, Mandsaur, M.P., India, with 12 treatment combinations, comprising four dates of sowing 25th September, 10th October, 25th October and 9th November with three stages of pinching i.e., No pinching, Pinching at 25 Days after sowing (DAS), Pinching 35 DAS. These treatments were replicated thrice in split spot design and analyzed. Treatment with 10th October sowing recorded maximum plant height, number of branches, fresh weight, dry weight, number of pods plant-1, pod length, weight of pod, number of seeds pod-1, weight of seeds pod-1, thousand seed weight, seed yield, straw yield, biological yield, harvest index, chlorophyll content, germination %, seedling vigour index, protein%, galactomannon content. While, 25th September sown crop took maximum days for 50% flowering and for maturity. Between pinching stages studied, Pinching at 35 DAS found to be superior in respect of number of branches plant-1, fresh and dry weight of plant (g) at harvest, number of pods plant-1, length of pod (cm), weight of pod (mg), number of seeds pod-1, weight of seeds pod-1 (mg), thousand seed weight (g), seed yield (q ha-1), straw yield (q ha-1), biological yield (q ha-1), harvest index (%), chlorophyll content in leaves at 75 DAS (SPAD), germination percentage of seeds, seedling vigour index, protein (%) and galactomannon in comparison to other pinching stages.